FRASA ADJEKTIVA BAHASA JEPANG: ANALISIS X-BAR - Puti Novianti Aristia (Center of Language and Cultural Studies, 2017)
The structure and principles of how to form adjective phrases in Japanese were investigated in this study. This qualitative study used content analysis as the research design and assigned Japanese Textbooks used for Japanese Course as the source of data. Corpus of Japanese utterances obtained from the textbook was selected as the research data, containing sentences, clauses, phrases, and discourses. Data were analyzed using linguistic theories of internal structure of tree diagram using X-bar. The study revealed that the structure of adjective phrases of Japanese served as the boundary sentence and pronoun. In addition, the principle of adjective phrases of Japanese consisted of: (1) adjective+noun, (2) pronoun+adjective, (3) noun+adjective, dan (4) adverb+adjective.